Ingratiation, Perceived Similarity Effects on Job Performance: The Mediating Role of Leader-Member Exchange - Hasana, Firda; Gunawan, Asep; Risdianto, Risdianto (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The metal business encounters significant market competition, compelling manufacturing companies to enhance human resource management to ensure consistent job performance. This study, based on Social Exchange Theory (SET), seeks to investigate the impact of Ingratiation and Perceived Similarity on Job Performance, with Leader-Member Exchange (LMX) serving as a mediating variable at PT. XYZ Indonesia. This study used a quantitative methodology to examine data from a saturated sample of 150 employees via the PLS-SEM technique through SmartPLS 4.0 software. The findings demonstrate that Ingratiation and LMX have significant and positive direct impacts on Job Performance. Conversely, Perceived Similarity does not directly influence Job Performance. LMX significantly mediates effects of both Ingratiation and Perceived Similarity on Job Performance. The integrated model effectively accounts for 72.7% of the variance in employee performance. The findings indicate that within the SET framework, cultivating high-quality supervisor-subordinate relationships is essential for enhancing workplace task productivity.